Structural Situation of Small Ruminant Enterprises in Mardin Province - Veysi ACIBUCA; Dilek BOSTAN BUDAK (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
The current study was undertaken to investigate the socio-economic characteristics, the situations of benefits from subsidies, the participation of union membership, and the animal care practices and problems of the small ruminants' farmers in Mardin. The study was conducted between February and June 2019 by analyzing self-reported questionnaire data involving 142 participant enterprises selected by stratified random sampling method in 4 districts of Mardin province. Analyzed data obtained from the study displayed that there was an average of 197.4 heads of animals in the enterprises, and 16.2% of the enterprises were engaged in livestock production only to meet their family needs. As the number of animals increased in the enterprises, the desire to reach the information and the situation of benefiting from the supports increased. Results obtained showed that the most important factors preventing the development of small ruminant farming activities in Mardin province were high feed costs and shepherd shortage. In line with this data, making the shepherding occupation attractive was suggested to tend young people to be employed in the small livestock-keeping activities.